Exploring the induction and measurement of positive affective state in equines through a personality-centred lens - Loni Loftus; Amy Newman; Matthew Leach; Lucy Asher (Scientific Reports)
Abstract There is increasing focus on how to induce and measure positive affective states in animals and the development of social license to operate has brought this to the forefront within equestrianism. This study aimed to utilise a range of methods to induce and measure positive affect in horses in real-world settings. Twenty healthy horses were scored for personality, exposed to four induction methods (wither scratching, high value food provision, positive reinforcement training and the addition of an affiliative conspecific), and data collected on their behaviour (QBA and ethograms) and physiology (heart and respiratory rate, heart rate variability, eye and ear thermography and salivary cortisol). Analyses identified potentially sensitive and specific behavioural (ear and eye position, QBA items, frustration items) and physiological (RR mean, HF power, LF power, LF/HF ratio, mean HR, RMSSD and pNN50) measures of affective state across the four quadrants of core affect. Individual difference effects were found, and personality traits such as unfriendly, nervous and unresponsive were associated with differing responses to induction stimuli indicating that all four induction stimuli are potentially useful for inducing positive affect depending on their salience to the individual. Research measuring and inducing positive affect in animals rarely considers personality, but this study underscores its importance. The dimensional approach taken allowed for assessment of the broad arousal and valence components of affect without ascribing measures to discrete emotions. Accurate, real-world measures of affect could benefit 116 million equines globally, and exploring ways to promote positive affect in horses can significantly enhance their welfare.